2005
DOI: 10.1055/s-2005-870198
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Metachronous Multiple Early Gastric Cancers after Endoscopic Mucosal Resection

Abstract: Annual endoscopic examinations can preserve the whole stomach in most patients with early gastric cancer after successful EMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
114
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 10 publications
11
114
3
1
Order By: Relevance
“…Similarly to the previous study [12], this study showed that new lesions tend to develop in the same third of the stomach with the same histologic features as the primary ones. Endoscopic resection can be applied as long as the new lesions are detected early enough to meet the criteria for it.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similarly to the previous study [12], this study showed that new lesions tend to develop in the same third of the stomach with the same histologic features as the primary ones. Endoscopic resection can be applied as long as the new lesions are detected early enough to meet the criteria for it.…”
Section: Discussionsupporting
confidence: 86%
“…In a previous study of metachronous gastric cancer after endoscopic resection, the overall incidence was reported to be 8.2 % during an average of 3.1 years of follow-up, and the cumulative 3-year incidence of metachronous gastric cancer was 5.9 % [19]. Another study reported that metachronous gastric cancers had an overall incidence of 14 % during a median of 57 months of follow-up [12], and yet another study showed the incidence of synchronous and metachronous multiple gastric cancers after endoscopic resection to be 14.5 and 8.5 %, respectively [15]. As highgrade dysplasia was also included in this study, the rate of synchronous or metachronous tumor development might be lower than that found in previous studies because of the lower invasiveness or multiplicity of dysplastic epithelium than invasive carcinoma.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…With regard to tumor location, it has been known that multiple gastric cancers arise more frequently in the middle and lower than in the upper third of the stomach [9-11, 21, 23]. In addition, during whole stomach endoscopic surveillance after endoscopic mucosal resection for early cancer, the incidence rate of metachronous cancer in the upper, middle, and lower third of the stomach has been reported to be 17, 33, and 50 %, respectively [24]. These results suggest that the middle and lower third of the stomach have foci of multicentric carcinogenesis more than the upper third of the stomach.…”
Section: Discussionmentioning
confidence: 99%